(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Exploring the national heritage in the linguistic aspect is the actual problem of nowadays. History and tradition of the Kazakh ethnic group saved in their language. Fairy tales is one of the oral literary folk genre in Kazakh literature. It reached to young generation as one of the richest genre. It helps psychological developing of young generation and helps to their minds. In fairy-tales examined as in verbal to speech and in literature. We tried to consider the fairy tale in psycholinguistic character. Fairy-tales helped listeners to develop their minds clearly convey their views, to distinguish the character of the people and understand the essence of fairy tales. In this article states that every child should understand that, in fairy tales have ethnical, psychological, suggestical influence.